Corrigendum: Quantitative clinical characteristics of 53 patients with MPS VII: a cross-sectional analysis - Zielonka, Matthias; Garbade, Sven; Kölker, Stefan; Hoffmann, Georg F.; Ries, Markus (Genetics in medicine, 2018)
Corrigendum: Quantitative clinical characteristics of 53 patients with MPS VII: a cross-sectional analysis